A role of geometry in the frame of competencies attainment - Anić, Ivan; Bokan, Neda; Šukilović, Tijana; Vukmirović, Srdjan (Teaching Mathematics and Computer Science, 2015)
We discuss aspects of the Education Reform from teaching to educational system. In this context we recognize some problems in recognition of some competencies that students need to achieve and we present how we have developed the measurement method of spatial abilities and problem solving competence. Especially, we investigate how students use spatial visualization abilities in solving various problems in other mathematical course. We have tested how students use their spatial abilities previously developed in geometry courses based on conceptual approach to solve a test based on procedural concept in Mathematical Analysis course.